Atresia of the Aortic Arch in 4-Year-Old Child: A Clinical Case Study - Nigro Stimato, Vittoria; Didier, Dominique; Beghetti, Maurice; Tissot, Cécile (Frontiers in Pediatrics, 2015)
Atresia of the aortic arch is a rare congenital heart defect with a high mortality when associated with other intracardiac defects. Cardiac Magnetic Resonance (CMR) provides the exact anatomy of the aortic arch and collateral circulation and is useful to diagnose associated aortic arch anomalies. This report describes the case of a 4 year-old child with atresia of the aortic arch, referred to our institution with the diagnosis of aortic coarctation and bicuspid aortic valve. On clinical exam, the femoral pulses were not palpable and there was a significant differential blood pressure between the upper and lower limbs. The echocardiography showed a severely stenotic bicuspid aortic valve but was limited for the exact description of the aortic arch. CMR showed absence of lumen continuity between the ascending and descending aorta distal to the left subclavian artery, extending over 5 mm, with the presence of a bend in the arch and diverticulum on either side of the zone of discontinuity, suggesting the diagnosis atresia of the aortic arch rather than coarctation or interruption. The patient benefited from a successful surgical comissurotomy of the aortic valve and reconstruction of the aortic arch with a homograft. The post-operative CMR confirmed the good surgical result. This case emphasizes the utility of CMR to provide good anatomical information to establish the exact diagnosis and the operative strategy.